Discovery and development of halal protease from Spondias cytherea for meat tenderization - Mat Noh, Nor Aini; Abdullah, Erna Normaya; Ahmad, Mohammad Norazmi (2018)
In this research, a novel protease from Ambarella (Spondias cytherea) was identified as a new potential halal meat tenderizer. Optimization of protease extraction by RSM has found the most optimized variables at pH 8.22, 4.95 % of TX-100, 6.80 mM of 2-mercaptoethanol, and 1.71 min of mixing time at 12.37 U/g of protease activity. The overall model was significant (P < 0.05) with R2 value of 0.9885. The enzyme was stable at pH 8.0 – 10.0 and temperature 50 – 60 °C. Incubation of enzyme with organic solvents showed higher activity in hydrophobic than hydrophilic phases. In addition, prolonged storage time of enzyme decreased the activity by 32 %. Protein bands of muscle proteins and firmness of muscle samples were reduced upon protease treatment. Moreover, at microstructural level, broken of tissues fiber and loosen of myofibrils were observed. From the results, it is determined that protease from Ambarella fruit can be used as an alternative source of proteolytic enzymes in meat tenderization.